A influência da arborização no microclima urbano : um estudo aplicado à cidade de Vitória, ES - Xavier, Tatiana Camello (2017)
Urbanization process causes many changes to the natural environment, among which the removal of a large part of vegetation and the alteration of surface materials, besides the inclusion of buildings and production of pollutants. These environment alterati